2017
DOI: 10.1063/1.4983962
|View full text |Cite
|
Sign up to set email alerts
|

Android worksheet application based on discovery learning on students’ achievement for vocational high school: Mechanical behavior of materials topics

Abstract: Abstract. This research reports a study of student worksheet based on discovery learning on Mechanical Behavior of Materials topics under Android application (Android worksheet application) for vocational high school. The samples are Architecture class X students of SMKN 4 (a public vocational high school) in Tangerang Selatan City, province of Banten, Indonesia. We made 3 groups based on Intellectual Quotient (IQ). They are average IQ group, middle IQ group and high IQ group. The method of research is used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Based on the analysis, it can be concluded that the use of the developed module can improve the ability in associating the concepts of physics with religious values that can be applied in life (Nanto, 'Aini, & Mulhayatiah, 2017;Suhendi, Mulhayatiah, & Zakwandi, 2018).…”
Section: The Students' Responsesmentioning
confidence: 99%
“…Based on the analysis, it can be concluded that the use of the developed module can improve the ability in associating the concepts of physics with religious values that can be applied in life (Nanto, 'Aini, & Mulhayatiah, 2017;Suhendi, Mulhayatiah, & Zakwandi, 2018).…”
Section: The Students' Responsesmentioning
confidence: 99%
“…But can use virtual labs as learning media (Sujanem et al, 2019). Fifth, situational (learning skills, contextual learning skills) are applied in laboratory activities, where material that is real can use a real laboratory, while material that is abstract can use a virtual lab (Nanto et al, 2017).…”
Section: Summarizing the Readingsmentioning
confidence: 99%
“…In pandemic situations that don't recognize whilst it's going to give up like this and rules are nonetheless changing, digital coaching substances are greater wished withinside the getting to know technique due to the fact they may be accessed every time and anywhere (Zhang et al, 2021;Kumar et al, 2021). One version of those coaching substances is e-module (Nanto et al, 2017).…”
Section: ▪ Introductionmentioning
confidence: 99%
“…The digital module presentations facts codecs in ee-e book layout electronically that is loaded onto a difficult disk, diskette, CD or flash disk and is examine the usage of digital gadgets which includes computers, etc. (Nanto et al, 2017;Permana, 2017). The improvement of e-modules ought to be according with the 2013 curriculum which expects college students to be professional in the usage of media, technology, facts and communication (ICT) wished withinside the twenty first century (Kemendikbud, 2017).…”
Section: ▪ Introductionmentioning
confidence: 99%